Dichlorodifluoromethane-carbon dioxide: A dielectric mixture as a sustainable alternative to SF6 in high voltage applications - Khan, Sajjad Ali; Habib, Salman; Khan, Muhammad Yasir Ali; Chauhdary, Sohaib Tahir; Ali, Abdar; Kamel, Salah; Elnaggar, Mohamed F. (Frontiers in Materials, 2023)
Sulphur hexafluoride (SF6) gas is the frequently consumed gas in High Voltage (HV) applications due to its high dielectric permittivity and arc-quenching property. However, due to its long Atmospheric Lifetime (AL), high Global Warming Potential (GWP), and other environmental concerns there is a need for a new sustainable gas as an alternative to SF6. Therefore, in this research, we present dichlorodifluoromethane (R-12) in conjunction with carbon dioxide (CO2) as an alternative. Compared to SF6, R-12 has 3,100 years shorter atmospheric lifetime and 15,400 less GWP. Moreover, CO2 is mixed with R-12 as a gas carrier to achieve a low boiling point as that of SF6. High Voltage Direct Current (HVDC), High Voltage Alternating Current (HVAC), and self-recoverability tests were conducted under varying concentrations of gas ratios at different pressures and a standard constant temperature. Comparison analysis showed that R-12 dielectric strength is close to that of SF6, and its mixture with CO2 possessed increased dielectric strength compared to a nitrogen and air mixture beyond 206.84 kPa. For HVAC and HVDC, a mixture of 50% R-12% and 50% CO2 establishes an unimpeachable ratio for HV applications. The mixture has self-recoverability properties and possesses positive synergism, which leads to the conclusion that the mixture of R-12 with CO2 enhances the dielectric strength compared to pure gases, as well as reduces costs.